1990
DOI: 10.1128/jvi.64.12.6027-6039.1990
|View full text |Cite
|
Sign up to set email alerts
|

Proteins encoded by the bovine papillomavirus E1 open reading frame: expression in heterologous systems and in virally transformed cells

Abstract: The E1 open reading frame (ORF) of bovine papillomavirus type 1 is required for the persistence of viral genomes as multicopy plasmid molecules in transformed rodent fibroblasts. E1 has been reported to contain two separate complementation groups (M and R, corresponding to N- and C-terminal domains, respectively) which regulate viral replication. However, E1 behaves as a single gene with respect to cell transformation and viral transcription. We examined the proteins translated from the entire ORF by using thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 53 publications
(40 reference statements)
1
27
0
1
Order By: Relevance
“…Biological materials. The cell lines employed for preparing soluble extracts for cell-free replication, the recombinant baculoviruses used for expressing the BPV1 proteins into Sf9 cells, and the antibodies able to recognize these proteins were described previously (4,42,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological materials. The cell lines employed for preparing soluble extracts for cell-free replication, the recombinant baculoviruses used for expressing the BPV1 proteins into Sf9 cells, and the antibodies able to recognize these proteins were described previously (4,42,44).…”
Section: Methodsmentioning
confidence: 99%
“…Two viral proteins, E1 and E2, are normally required for replicating PV DNA (54). E1 is similar to another well-studied viral initiator protein, SV40-polyomavirus large T antigen (10): E1 is a nuclear phosphoprotein (42,51) with DNA helicase and ATPase activities (30,44,46,59) that is able to recognize and unwind an 18-bp palindrome within the viral replication origin (47,49,55,56,59). PV origins are short sequences (less than 100 bp) comprising mainly an E1 binding site and important flanking elements (see, for instance, references 14 and 53) such as AT-rich sequences and one or several binding sites for the second viral protein, transactivator E2.…”
mentioning
confidence: 99%
“…Amino acid similarities suggested that El, like SV40 large-T antigen, may be a DNA helicase/ATPase involved in initiating viral DNA replication (3). Subsequently, BPV-1 El protein was shown to be a nuclear 68-72 kD ATP-binding phosphoprotein (4,5,6). A mutation in El (Pro-434 to Ser), analogous to that in the SV40 large-T antigen mutant tsA209 that impairs ATPbinding, renders BPV-1 defective for DNA replication and abolishes ATP-binding by El (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore likely that the differences between SV40 and BPV1 lie with the proteins involved in the initiation of replication. The E1 protein, which shares a number of biochemical properties with the T antigen, has been clearly established as the initiator of BPV1 replication (33,35,36,43,52). The role of the E2 transactivator protein in BPV1 replication is less clear.…”
mentioning
confidence: 99%